Ageism and age discrimination in working life. Issue 3 (2nd July 2016) - Solem, Per Erik
Abstract: The current demographic shifts call for prolongation of working life and postponed retirement in most industrialized nations. The success of policies promoting this, depends on a range of factors, one of them is the amount of ageism and age discrimination in working life. This article explores the cognitive, affective and behavioural aspects of ageism in working life in Norway. Data are from the Norwegian Senior Policy Barometer 2013 consisting of two national samples, one of 1003 employed persons, and one of 751 managers in private and public companies. The results show that the conceptions of older workers are in some ways quite positive, as managers think of workers above age 50 as performing at least as well as younger workers. Yet, managers tend to hesitate to call in applicants in their late 50s, to job interviews. This hesitation is correlated with less liking for recruiting "seniors" and "older workers", indicating that the affective element of ageism needs attention in prevention of age discrimination. Contact and knowledge may have positive effects, since managers are ranking "seniors" and "older workers" higher for retention than for recruitment. As the public sector is becoming more similar to the private sector in market orientation, the relatively good position of older workers in the public sector may become challenged. Further research should explore the strategies of age blindness versus age diversity celebration for promotion of employment among older citizens.